(untitled) (ENTHYMEMA, 2022)
What did a Russian peasant’s ‘mental map’ look like between 1917 and the consolidation of the Soviet order in 1934? To what extent does a specific province or oblast have a place on this map? Was ‘provincial Russia’ how peasants thought about the vast non-urban territory in transition? Provincial identity is an elusive category during any period – it was not the mental or physical space in which peasants lived. They resided in a village, were members of a parish encompassing several neighboring communities, and had contact with larger geographical units when they bought and sold goods, left for work in towns or cities, or were called up for military service. The fact that provincial identity is difficult to quantify does not make it insignificant, and, with the help of rural literature and oral histories, this paper will track provincial and regional ties among peasants for this period.